It is an organ, it is new, but it is not a new organ. Conceptualizing language from a homological perspective - Balari, Sergio; Lorenzo, Guillermo (Frontiers in Ecology and Evolution, 2015)
It is a widely shared opinion among specialists that language is an evolutionary innovation, or that it contains some key evolutionary innovations. However, such claims are not based on a correspondingly consensual concept of ‘evolutionary innovation,’ but are rather expressed on atheoretical grounds. This fact has thus far acted as an obstacle for the collaborative effort upon which the task of disentangling the evolution of this human capacity should be built. In this paper, we suggest a formal approach to the issue, based on Günter Wagner’s recent theory of homologies and novelties. Within this new framework, we conclude that language is the human instantiation (thus an ‘homolog’) of a character widely represented in the nervous system of animals, which incorporates a number of interdependent innovative states that allows us conceptualizing it as a ‘variational modality’ of this ancient organ.